Physics of Complex Colloids - Bechinger, C. (IOS Press, 2013)
Colloids are systems comprised of particles of mesoscopic size suspended in a liquid. They have recently been attracting increased attention from scientists and engineers due to the fact that they are nowadays present in many industrial products such as paints, oil additives, electronic ink displays and drugs. Colloids also serve as versatile model systems for phenomena and structures from solid-state physics, surface science and statistical mechanics, and can easily be studied using tabletop experiments to provide insight into processes not readily accessible in atomic systems.